2020
DOI: 10.1016/j.smr.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of soccer referee experiences in France and the Netherlands: Abuse, conflict, and level of support

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 61 publications
1
39
1
Order By: Relevance
“…This is especially critical for those who participate in high-level competitions. Programs dedicated to football referees and their training exist in all EU countries, for example, in France, Belgium, and the Czech Republic [28][29][30][31]. In the Czech Republic, there is a program for training and advanced training of football referees.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially critical for those who participate in high-level competitions. Programs dedicated to football referees and their training exist in all EU countries, for example, in France, Belgium, and the Czech Republic [28][29][30][31]. In the Czech Republic, there is a program for training and advanced training of football referees.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst football referees, research has shown that due to non-accidental violence, many officials are leaving the sport, in some cases rendering amateur levels of play unsustainable. 11 In football, the majority of mental health research has focused on players, with limited consideration given to referees. Unfortunately, such a shallow research pool has resulted in a deficit of knowledge which prevents not only the understanding of mental health symptoms and disorders in this population but also the creation of evidence-based interventions.…”
Section: Introductionmentioning
confidence: 99%
“…As happened in France and the Netherlands, referees often feel that they have been subjected to verbal or physical abuse during football matches. [9] It is an obstacle in football matched that must be faced by referees. [10] Referees who are able to face various obstacles during the match show how good and quality the referee's performance is in leading the match.…”
Section: Introductionmentioning
confidence: 99%